Body composition, body indexes and somatotype in university handball players - López García, Ricardo; Lagunes Carrasco, José Omar; Cruz Castruita, Rosa María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The aim of this study was to determine body composition, body indexes and somatotype in handball players. Forty-eight players (21 men and 27 women) from a university team were evaluated. Anthropometric measurements were performed to obtain fat percentage, muscle mass, body indexes and somatotype. The results showed that the men had 11.82% body fat, with a meso-endomorphic somatotype. On the other hand, 22.49% and mesomorphic-endomorphic somatotype in women. These data are relevant to be able to make comparisons with top level players and to improve the body composition of athletes to try to achieve the best possible performance.